Assessment of Radon Concentrations in the Soil of South Baghdad Suburbs - Amin, Sahar Ahmed; Al-Khateeb, Mukdad Abd Al-Wahaab; Al Shammari, Talib Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Measurements of radon gas concentrations were carried out for 12 soil samples at 3 sampling depths (surface, 5 cm and 10 cm) collected from (4) locations in south Baghdad suburbs (Bu'aitha) using solid state nuclear track detector CR-39 and sealed can technique. Radon concentrations for surface samples were ranged from 402.2 to 1538.4 Bq.m-3 with an average 994.4 Bq.m-3. Whereas, radon concentration was ranged from 813.1to 2050.4 Bq.m-3 and from 1309.8 to 4626. 1Bq.m-3 with an average values of 1359.8 Bq.m-3 and 2338.3 Bq.m-3 for 5 cm and 10 cm depths respectively. Maximum radon level was found at the location near to the river (site S4) while the minimum radon level was found at residential area (site S2). Radium contents were ranged from 0.42 to 1.62 Bq.kg-1, from 0.85 to 2.15 Bq.kg-1 and from 1.38 to 4.86 Bq.kg-1 with average values of 1.04, 1.43 and 2.46 Bq.kg-1 for surface, 5 cm and 10 cm depths respectively. Radon exhalation rates as a function of area and mass were also obtained. Surface exhalation rate ranged from 0.05 to 0.18 Bq.m-2.h-1, from 0.09 to 0.24 Bq.m-2.h-1 and from 0.15 to 0.53 Bq.m-2.h-1 with average values 0.11, 0.16 and 0.27 Bq.m-2.h-1 for surface, 5 cm and 10 cm depths respectively. Mass exhalation rate ranged from 0.02 to 0.06 Bq.kg-1.h, from 0.03 to 0.08 Bq.kg-1.h and from 0.05 to 0.18 Bq.kg-1.h with average values 0.04, 0.05 and 0.09 Bq.kg-1.h for surface, 5 cm and 10 cm depths respectively. The results obtained from this study indicate that the region background radiation levels are within the natural limits.